Bromo-Substituted Salamo-Type Compounds Possessing More Flexible O-Alkyl Chain: Synthesis and Sructural Characterization - Jin1, Bo-Xian; Gao2, Su-Xia; Zhou1, Wei-Min; An1, Gao-Xian; Bai1, Yang; Du1, Wei; Dong1, Xiu-Yan (Asian Journal of Chemistry, 2014)
A series of bromo-substituted Salamo-type compounds have been synthesized by the reaction of 5-bromo-2-hydroxybenzaldehyde with 1,7-bis(aminooxy)heptane, 1,8-bis(aminooxy)octane, 1,9-bis(aminooxy)nonane or 1,10-bis(aminooxy)decane in hot ethanol medium, respectively, and characterized by elemental analyses, IR, UV-visible spectra and 1H NMR spectroscopy.